2015
DOI: 10.4094/chnr.2015.21.3.272
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Experience of Parents with Chronically Ill Children

Abstract: Purpose: The purpose of the study was to describe the parenting experience of parents of children with chronic illness in Korea. Methods: A conventional contents analysis was used for the study. Twelve mothers of chronically ill children participated in the study. Qualitative data were analyzed using the Morse and Field method. Results: Four categories, 10 subcategories and 42 codes emerged from the data on the parenting experience of parents of children with chronic illness. The four categories were 'Sacrific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
4
4
0
1
Order By: Relevance
“…In addition, we found that modification of the family's life pattern, the family's own know‐how and renormalization of life by accepting symptom management behaviour as a component of daily life were protective factors for the salutogenic sense of health in adolescents with Moyamoya disease. These findings are similar to those of a previous study by Park et al (2015), who explored the experiences of parents raising children with chronic diseases. In Park et al's (2015) study, parents gradually adapted to the child's disease process, naturally accepted the disease management as a daily routine and established a new routine by considering the disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we found that modification of the family's life pattern, the family's own know‐how and renormalization of life by accepting symptom management behaviour as a component of daily life were protective factors for the salutogenic sense of health in adolescents with Moyamoya disease. These findings are similar to those of a previous study by Park et al (2015), who explored the experiences of parents raising children with chronic diseases. In Park et al's (2015) study, parents gradually adapted to the child's disease process, naturally accepted the disease management as a daily routine and established a new routine by considering the disease.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to those of a previous study by Park et al (2015), who explored the experiences of parents raising children with chronic diseases. In Park et al's (2015) study, parents gradually adapted to the child's disease process, naturally accepted the disease management as a daily routine and established a new routine by considering the disease. Moreover, Knafl et al (2010) emphasized the role of health‐care providers in supporting the normalization of the family by balancing disease management and daily family life.…”
Section: Discussionsupporting
confidence: 91%
“…Parents of children with chronic illness in South Korea tend to devote themselves and sacrifice other aspects of their life to focus only on the child’s treatment. Consequently, their parenting practices change as their lives renormalize (Park, Lee, Oh, Im, & Cho, 2015). Particularly in South Korea, where rates of pediatric cancer survival are high (Korea Central Cancer Registry, National Cancer Center, 2017), how mothers choose to parent their child with cancer can be unique.…”
Section: Rationalementioning
confidence: 99%
“…것으로 알려졌다 (Lim & Kim, 2013;Park et al, 2015;Chei et al, 2000). 서는 성 성숙과 신체상 및 자아 존중감 성 (Park et al, 2006), 숙 정도에 따른 신체상 성숙불안 등의 , (Park & Kim, 2016) 연구가 시도 되었으며 성조숙증 여아의 우울과 성숙불안에 대 한 연구는 부족한 실정이다.…”
Section: 의 치료기간은 년 정도로 성조숙증 아동은 치료기간 동안 2~3unclassified